The effect of Toxoplasmosis on Hematological and Biochemical Parameters in Pregnant Women in Thi-Qar Province - Dawood S. Mahdi1, A.H. Awad2, Abeer T. Ali1 (Institute of Medico-legal Publications Pvt Ltd, 2020)
The aim of the present study was to detect the effect of infection with Toxoplasma gondii on hematological and biochemical parameters in pregnant women. Blood samples (103) were collected from emergency unit of Bent Al-Huda Hospital in Thi-Qar province during the period from October 2018 till March 2019. Samples gave agglutination results with latex test (79) were tested with ELISA test. Ten blood samples were collected from healthy pregnant women as control. Concentration of blood hemoglobin (Hb), total WBCs count, liver enzymes Glutamate Oxaloacetate Transaminase (GOT) and Glutamate Pyruvate Transaminase (GPT), lipid profile (total Cholesterol and Triglycerides) were estimated during this study using different commercial Kits.